PENGARUH FASILITAS SEKOLAH DAN MOTIVASI GURU TERHADAP EFEKTIVITA PROSES MENGAJAR DI MADRASAH ALIAYAH DDI BONTANG - Martopan Abdullah (UNIVERSITAS MUHAMMADIYAH METRO, 2018)
Martopan Abdullah. Drivers of School Facilities and Motivation of Teachers on the Effectiveness of the Teaching and Learning Process at Bontang DDI Madrasah. The teacher is one component that deals directly with the subject of students, must have the ability / compotency because it determines the quality of the learning process and the learning outcomes of students. Based on this, researchers are encouraged to analyze the teacher's potential by looking at the differences in the average teacher's composition in terms of motivation the teacher addresses the effectiveness of the teaching and learning process especially the teacher who teaches at Bontang DDI Madrasah Aliyah. This type of research is quantitative with 34 sample teachers in Bontang DDI Madrasah. from 34 populations. Data on teacher potency were collected using instruments in the form of tests developed on a Likert scale and questionnaire techniques. The data were analyzed using quantitative analysis, ie with multiple regression and ANOVA (SPSS 20) in one pathway at a 5 percent level of significance (5% ). The results of the study showed that there was an influence of facilities and teacher motivation on the effectiveness of the teaching and learning process in Bontang DDI Madrasah. In terms of training and experience in presenting material. Scientific facts found in this study indicate that the influence of school facilities and teacher motivation on the effectiveness of the learning process is enhanced by training. It is expected that teachers can develop their competence through several activities to further enhance work or teaching experience. Keywords: School Facilities, Teacher Motivation, Effectiveness of the Teaching Process